Sex Difference in the Association of Osteoporosis and Osteopenia Prevalence in Patients with Adrenal Adenoma and Different Degrees of Cortisol Excess - Shoichiro Izawa; Kazuhisa Matsumoto; Kazuhiko Matsuzawa; Takuyuki Katabami; Takanobu Yoshimoto; Michio Otsuki; Masakatsu Sone; Yoshiyu Takeda; Shintaro Okamura; Takamasa Ichijo; Mika Tsuiki; Tomoko Suzuki; et al. (International Journal of Endocrinology)
Objective. Osteoporosis and osteopenia (OS/OP) are frequent in patients with adrenal adenomas associated with cortisol excess (CE). However, the relationship between OS/OP and CE severity considering sex differences is unknown. Design. A cross-sectional observational study from January 2006 to December 2015. Patients. 237 patients with adrenal adenoma associated with CE, including Cushing’s syndrome and mild autonomous cortisol secretion (MACS), diagnosed in 10 referral centers in Japan. MACS was defined by 1 mg overnight dexamethasone suppression test (DST) cortisol level >1.8 μg/dL. Measurements. Prevalence of fragility fractures, medication for osteoporosis, and bone mineral density. Results. In total, 112 of 237 patients, who were predominantly female (P<0.001) and had lower BMI (P=0.013), had OS/OP. Patients with OS/OP was significantly affected by CE (P<0.01) than those without. The adjusted odds ratio (OR) for predicting OS/OP was obtained in multivariate logistic regression analysis. Clinical measures of CE, 1 mg DST cortisol levels, were positively associated with OS/OP in total cases (OR 1.124, 95% CI: 1.070–1.181, P<0.001) and the cases with MACS (OR 1.156, 95%CI: 1.046–1.278, P=0.005). A cutoff value of 1 mg DST cortisol level >5.0 μg/dL was associated with OS/OP differently between men and women. OS/OP risk in men with MACS was significantly affected only by 1 mg DST cortisol levels. However, OS/OP risk in women with MACS was significantly affected by 1 mg DST cortisol levels and age. Conclusions. CE severity in adrenal adenoma is positively associated with OS/OP. However, the associated factors of OS/OP in the patients with MACS are different between men and women.